Flower morphology and plant–bee pollinator interactions are related to stamen dimorphism in Melastomataceae. (6th November 2021) - Valadão‐Mendes, L. B.; Rocha, I.; Meireles, D. A. L.; Leite, F. B.; Sazima, M.; Maruyama, P. K.; Brito, V. L. G.
Abstract: Approximately 20, 000 species of flowering plant offer mainly pollen to their pollinators, generally bees. Stamen dimorphism, a floral trait commonly present in some pollen flowers, is thought to be associated with exclusive pollen provision for highly effective bee pollinators. Notwithstanding, little is known about how stamen dimorphism is related to other floral morphological traits and, consequently, plant–pollinator interactions at the community scale. Here we investigated the relationship between stamen dimorphism and other floral morphological traits, as well as the interactions with pollinators in plants of Melastomataceae. We characterized each plant species as stamen dimorphic or stamen isomorphic according to differences in size and shape between stamen sets. Data on interactions between the plants and their bee pollinators were analysed as quantitative bipartite networks. We found that petal and style size and shape were correlated to stamen dimorphism. Stamen dimorphic species present larger flowers and less variable style shapes than stamen isomorphic species. Furthermore, stamen dimorphism is associated with higher richness of visiting bees, i.e . higher ecological generalization. During the evolutionary history of Melastomataceae, the dependence on pollinators for fruit set has possibly favoured the evolution of larger flowers with dimorphic stamens, which in turn are able to make use of a larger spectrum of pollen‐collecting bees, leading to ecological generalization. Abstract : Stamen dimorphic species present larger flowers, have less variable style shapes and are associated with greater richness of visiting bees than stamen isomorphic species.